Hanging out : community-based after-school programs for children - Garner, Ruth; Zhao, Yong, 1965-; Gillingham, Mark G. (Bergin & Garvey, 2002)
There is an unsettledness now in after-school childcare. The stay-at-home mom years are largely over. Will children, even very young children, stay home alone or hang out with peers, risking loneliness or engaging in problem behavior? Will some new form of supervised care emerge? The authors in this collection have spent time in community after-school programs and have learned what happens there. The authors suggest that after-school programs can be an important part of a system of childcare--as long as we can find ways to build programs for small and scattered populations as well as for densely packed ones, and as long as the money to fund programs can be found. The money is important. Many of the programs discussed in this book are specifically targeted to children from families with low incomes. These are the families least likely to be able to pay for care. A reader leaves this book with both anxiety and hope about the future of childcare in the United States.